A neuroscience perspective of the gut theory of Parkinson's disease. (28th February 2018) - Smith, Lisa M.; Parr‐Brownlie, Louise C.
Abstract: Parkinson's disease is caused by complex interactions between environmental factors and a genetic predisposition. Environmental factors include exposure to pesticides and toxins, heavy metals and accumulation of iron and/or manganese in the brain. However, accumulating evidence indicates that gut–brain health and function are impaired in Parkinson's disease, often a decade before motor symptoms are diagnosed. We present the gut–brain theory of Parkinson's disease and summarise the peripheral and central nervous system pathology, gastrointestinal symptoms experienced by many Parkinson's patients, the route by which gut–brain dysfunction may occur and changes in gut microbiota that are associated with disease expression. Finally, we consider future gut‐based treatments to prevent or slow down the progression of Parkinson's disease and explore whether this knowledge may highlight biomarkers to be included in complex algorithms in the future to assess a person's risk of developing Parkinson's disease. Abstract : Gut–brain dysfunction often occurs a decade before the motor symptoms of Parkinson's disease are diagnosed. α‐Synuclein accumulates in peripheral and central nervous systems in patients and is associated with changes in gut microbiota and function. This knowledge maybe used in the future as part of a complex risk assessment for Parkinson's disease and vagus nerve transections and faecal transplants could be used to reduce risk or treat the disease.